Walizka, peron, wagon… Uchodźczy los we Wspomnieniach Nadieżdy Teffi - Bielniak, Nel (Przegląd Wschodnioeuropejski, 2024)
The first-wave Russian emigrants who left the country as a result of the October Revolution in 1917 and the civil war were united by a deep awareness of the loss of their roots and the need to preserve the memory of their former homeland and the tragic historical events that contributed to the exodus. Hence the huge popularity of the so-called “memory” literature among emigre writers and its diversity. The aim of this article is to include Memoirs of Nadezhda Teffi in the memoirs of the first wave of Russian emigration, dealing with the subject of the civil war and escape from Sovdepia. Typical distinguishing features of the reggee fate related to the category of memory were analysed, which include a suitcase, a platform and a wagon (similarly: a trunk, a harbor, a cabin). These attributes (except for a suitcase) did not attract the attention of researchers, although the plot of the work, which is the author’s subjective account, is largely focused around them. As a result, it was proved that they played various roles in the biographies of emigrants, reflecting new realities and social moods, often going far beyond their usual purpose or becoming symbols. This allows us to conclude that in her memoirs, Teffi combines the individual and collective dimension of remembering, because she shows a breakthrough moment in the history of the homeland from the narrator’s individual perspective through the details of everyday life, and is also part of the mission of Russian émigré literature by co-shaping the memory of the recent past.